FORMULATION OF ALOE VERA (Aloe vera L.) EXTRACT GEL AS A SKIN MOISTURIZER WITH VARIATIONS OF CARBOPOL 934 - Ramdhini, Rizki Nisfi; Anggraini, Cici Selvia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Aloe vera is a type of plant that can moisturize the skin to prevent premature aging. One type of cosmetic preparation that can be used for skin health is gel. This research aims to determine the optimal variation of Carbopol 934 for formulating the gel. The method used in this research is maceration, creating aloe vera extract gel preparations in three formulas with variations of Carbopol 934: F1 (1 g), F2 (1.5 g), and F3 (2 g). Subsequently, a physical evaluation was conducted, which included: Organoleptic test: The results showed a nearly yellowish-white color, a characteristic aloe vera plant aroma, and a semi-solid form. pH measurement: The pH values for F1, F2, and F3 were 6.1, 4.8, and 4.3, respectively.Homogeneity test: All formulas were homogeneous. Viscosity test: The viscosity results for F1, F2, and F3 were 285,290, 515,821, and 749,374 mPa.s, respectively, compared to the reference sample at 375,163 mPa.s. Spreadability test: The spreadability for F1, F2, and F3 were 6.5 cm, 5.5 cm, and 5 cm, respectively. Adhesion test: The adhesion times for F1, F2, and F3 were 7.02, 10.40, and 24.23 seconds, respectively. Based on the physical evaluation results, the gel preparations meet the requirements for a good gel preparation according to the specified SNI No.06-2588 standards.